2009
DOI: 10.1002/ardp.200900050
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Activators as Synaptogenic and Memory Therapeutics

Abstract: The last decade has witnessed a rapid progress in understanding of the molecular cascades that may underlie memory and memory disorders. Among the critical players, activity of protein kinase C (PKC) isoforms is essential for many types of learning and memory and their dysfunction, and is critical in memory disorders. PKC inhibition and functional deficits lead to an impairment of various types of learning and memory, consistent with the observations that neurotoxic amyloid inhibits PKC activity and that trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 175 publications
0
16
0
3
Order By: Relevance
“…Overexpression of PSD-95 converts silent synapses to functional synapses (58), whereas synaptophysin may be required for increased presynaptic vesicle density, thereby facilitating neurotransmitter release (59). We found that overexpressing PKC⑀ in primary human neurons induces the mRNA and protein levels of PSD-95 and synaptophysin, whereas knockdown of PKC⑀ reduces PSD-95 and synaptophysin mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 76%
“…Overexpression of PSD-95 converts silent synapses to functional synapses (58), whereas synaptophysin may be required for increased presynaptic vesicle density, thereby facilitating neurotransmitter release (59). We found that overexpressing PKC⑀ in primary human neurons induces the mRNA and protein levels of PSD-95 and synaptophysin, whereas knockdown of PKC⑀ reduces PSD-95 and synaptophysin mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 76%
“…Pharmacological restoration of the impaired PKC function results in an enhanced memory capacity and synaptic remodeling/repair and synaptogenesis and therefore represents a potentially important strategy for the treatment of memory disorders, such as Alzheimer disease (25,28,52). Here we showed that PKC activators protect against A␤ toxicity.…”
Section: Discussionmentioning
confidence: 79%
“…Bryostatin 1 passed phase-I and -II, but not phase-III, clinical trials, as a cancer treatment, alone and in combination with other chemotherapy agents (Trindade-Silva et al, 2010). It has been used in applications for the central nervous system (Sun & Alkon, 2009). Bryostatin 1 has initiated phase-II clinical trial for Alzheimer's disease (Etcheberrigaray et al, 2004) and has been proposed as a possible therapy for the human immunodeficiency virus (Mehla et al, 2010).…”
Section: Bryostatinmentioning
confidence: 98%